Use of Customized 3D-Printed Titanium Augment With Tantalum Trabecular Cup for Large Acetabular Bone Defects in Revision Total Hip Arthroplasty: A Midterm Follow-Up Study - Kong, Keyu; Zhao, Chen; Chang, Yongyun; Qiao, Hua; Hu, Yi; Li, Huiwu; Zhang, Jingwei (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Aims: In revision total hip arthroplasty (THA), large acetabular bone defects pose challenges for surgeons. Recently, wide application of trabecular tantalum, which has outstanding biocompatibility and mechanical properties, and the development of three-dimensional (3D) printing have led to the introduction of new schemes for acetabular reconstruction. However, few studies have focused on the treatment of bone defects with customized 3D-printed titanium augments combined with tantalum trabecular cup. Thus, we aimed to evaluate the effect of this therapy in patients who underwent revision THAs. Patients and Methods: We included 23 patients with Paprosky type III acetabular bone defects who underwent revision THA between January 2013 and June 2019. The preoperative hip rotation center and functional score were compared with those at 2–7 years (average 4.7 years) postoperatively to evaluate the midterm prognosis of our treatment choice. Results: Postoperatively, the rotation centres of all hips were comparable with those of the contralateral hips. Hip function improved with average Harris Hip Score improved from 33.5 (22.7–40.2) to 86.1 (73.5–95.6) and average Oxford Hip Score improved from 8.3 (0–14) to 38.8 (35–48) during follow-up. One dislocation, which occurred due to extreme hip flexion within 6 weeks, was treated with closed reduction, and no recurrent dislocation occurred. No nerve injury, infection, aseptic loosening, or osteolysis were observed and no re-revision was performed in any patient. Conclusion: Satisfactory midterm outcomes were obtained with 3D-printed titanium augment combined with tantalum cup for the treatment of acetabular defects in revision THA. Changes in the Harris Hip Score and Oxford Hip Score suggested a significant improvement in hip function.